Terminating Anode Effects by Lowering and Raising the Anodes - A Closer Look at the Mechanism - Thonstad, J; Vogt, H (Light Metals 2010 - Proceedings of the Technical Sessions Presented by the TMS Aluminum Committee at the TMS 2010 Annual Meeting and Exhibition, Seattle, Washington, USA, February 14-18, 2010, 2010)
In the aluminium industry anode effects are unwanted events, leading to a waste of energy, overheating and emissions of PFC gases that have a high environmental impact. A common way to quench anode effects in prebake cells is to lower and raise the anodes repeatedly, so-called "anode pumping". This method is normally very effective, the anode effect normally going off after a few cycles. The actual mechanism has been the subject of some controversy, explanations varying from: (1) the effect of exposing fresh anode surface area when lowering the anodes, (2) decreased anode current density due to larger active anode surface area, or (3) making short-circuits to the metal pad. Based on a mathematical model the present work discusses the mechanism, focusing on the enhancement of the anode surface area.